New co-drawing strategies for the fabrication of glass/polymer fibers - Strutynski Clément; Deroh Moise; Bizot Rémi; Evrard Marianne; Désévédavy Frédéric; Gadret Grégory; Brachais Claire-Hélène; Kibler Bertrand; Smektala Frédéric (EPJ Web of Conferences, 2023)
Among the different fundamental aspects that govern the design and development of elongated multimaterial structures via the preform-to-fiber technique, material association methodologies hold a crucial role. They greatly impact the number, complexity and possible combinations of functions that can be integrated within single fibers, thus defining their applicability. In this work, co-drawing strategies to produce monofilament microfibers from unique glass-polymer associations are discussed.